COUPLING ERUPTION AND TSUNAMI RECORDS: THE KRAKATAU 1883 CASE STUDY, INDONESIA - Paris R.; Wassmer P.; Lavigne F.; Belousov A.; Belousova M.; Iskandarsyah Y.; Benbakkar M.; Ontowirjo B.; Mazzoni N. (My University, 2014)
The well-documented 1883 eruption of Krakatauvolcano (Indonesia) offers an opportunity to couple the erup-tion’s history with the tsunami record. The aim of this paper isnot to re-analyse the scenario for the 1883 eruption but todemonstrate that the study of tsunami deposits provides infor-mation for reconstructing past eruptions. Indeed, though thecharacteristics of volcanogenic tsunami deposits are similar tothose of other tsunami deposits, they may include juvenilematerial (e.g. fresh pumice) or be interbedded with distal pyro-clastic deposits (ash fall, surges), due to their simultaneity withthe eruption. Five kinds of sedimentary and volcanic faciesrelated to the 1883 events were identified along the coasts ofJava and Sumatra: (1) bioclastic tsunami sands and (2) pumi-ceous tsunami sands, deposited respectively before and duringthe Plinian phase (26–27 August); (3) rounded pumice lapillireworked by tsunami; (4) pumiceous ash fall deposits and (5)pyroclastic surge deposits (only in Sumatra). The stratigraphicrecord on the coasts of Java and Sumatra, which agrees partic-ularly well with observations of the 1883 events, is tentativelylinked to the proximal stratigraphy of the eruption.
Keywords: 38.37.25 Вулканология; Кракатау (Индонезия); Volcanic tsunami; Tsunami deposits; 1883 Krakatau eruption; Pyroclastic fall; Pyroclastic surge; Indonesia